La transparencia en el arbitraje internacional y en los tratados bilaterales de inversión - Febles Pozo, Nayiber (Universitat de Girona, 2019)
The thesis's main objective is the analysis of transparency in international arbitration. To this purpose, we start from a broad conception of the notion of transparency and its relevance in the current Bilateral Investment Treaties (BITs) and in the main international arbitration regulations: the ICSID, the ICC, UNCITRAL and its Rules on Transparency in Treaty-based Investor-State Arbitration, followed by a study of the most important issues of the arbitration procedure related to transparency, such as public hearings, the participation of third parties in the procedure (third-party funders and amicus curiae), the appointment of arbitrators and the conflict of interests and, finally, the analysis of transparency in the decisions (arbitral awards). The thesis proposes and bases, among other issues, the need to create an ICSID Court of Appeal and, if not, the most suitable mechanism for the implementation of an International Investment Tribunal
Keywords: Advertising; Arbitrage; Arbitragem; Arbitraje internacional; Arbitration; Bilateral Investment Treaties (BITs); Confidencialidad; Confidencialitat; Confidentiality; Ethical principles; International Arbitration; International Investment Tribunal; Investments; Investor-state arbitration; Preciding; Principios éticos; Principis ètics; Publicidad; Publicitat; Transparencia; Transparency; Transparència